HUBUNGAN ANTARA IMT DENGAN HIPERKOLESTEROLEMIA PADA MAHASISWA LAKI-LAKI USIA 18-22 TAHUN DI FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Via Diarisma Anggarika; Ari Udiyono; Henry Setyawan Susanto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Non infectious diseases has become a public health problem that is quite large in Indonesia. One of the causes of diseases such as hypertension, stroke and heart diseases are caused by hypercholesterolemia, even the  death offen happened to the people who suffered  hypercholesterolemia. The purpose of this study is to determine the factors which associated with hypercholesterolemia in men aged 18-22 years in the Faculty of Engineering of Diponegoro University.Type of the research is observational research with cross-sectional study design, the sample of the study was male students aged 18-22 years in the Faculty of Engineering UNDIP of 100 people. Univariate analysis used  frequency distribution, bivariate correlation used test Rank Spearman. Results of bivariate analysis showed an association between BMI (p = 0.0001; r= 0392) with hypercholesterolemia. Need awareness cholesterol screening regularly for at least three months to prevent the occurrence of hypercholesterolemia and other cardiovascular disease risk.